2010
DOI: 10.1002/cjas.144
|View full text |Cite
|
Sign up to set email alerts
|

A multidimensional analysis of supply chain integration in canadian manufacturing

Abstract: Supply chain management is a key element in companies' competitiveness. We surveyed 512 Canadian manufacturers, most of which were small or medium‐sized enterprises (SMEs). Our survey was structured around four dimensions of supply change integration, namely: nesting, collaboration, financial incorporation, and distancing. In this paper we describe the use of supply chain management practices and show that their use is dependent on the nature of the business partners (i.e., upstream or downstream positioning o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…The inter-relation between SCM practices, operational capabilities and performance have been emphasised by Hsu et al (2009) and Robb et al (2008). Country studies also reveal the impact of SCM adoption on performance (Olhager & Selldin, 2004;Zhou & Bento, 2007;Koh et al, 2007;Chow et al, 2008;Robb et al, 2008;Halley & Beaulieu, 2010). However, Basnet et al (2003) identified the status of SCM practices at manufacturing companies in New Zealand and verified that the adoption is not well disseminated.…”
Section: Literature Reviewmentioning
confidence: 91%
See 4 more Smart Citations
“…The inter-relation between SCM practices, operational capabilities and performance have been emphasised by Hsu et al (2009) and Robb et al (2008). Country studies also reveal the impact of SCM adoption on performance (Olhager & Selldin, 2004;Zhou & Bento, 2007;Koh et al, 2007;Chow et al, 2008;Robb et al, 2008;Halley & Beaulieu, 2010). However, Basnet et al (2003) identified the status of SCM practices at manufacturing companies in New Zealand and verified that the adoption is not well disseminated.…”
Section: Literature Reviewmentioning
confidence: 91%
“…However, evidence on the relationship between SCM adoption and performance is mixed. The influence of contextual factors (size, position, extension of the chain) in adopting SCM practices are emphasised by Li et al (2005Li et al ( , 2006; Halley and Beaulieu, 2010 additionally emphasise the company's position on the SC and the field of operation. The influence of the industry specific factors have been emphasised by Jharkharia and Shankar (2006) who studied four different types of industry (auto, engineering, fast moving consumer goods, process) in India.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations